Modeling the Allocation System: Principles for Robust Design Before Restructuring. Issue 2 (February 2015) - Mehrotra, Sanjay; Kilambi, Vikram; Gilroy, Richard; Ladner, Daniela P; Klintmalm, Goran B; Kaplan, Bruce
Abstract : The United Network for Organ Sharing is poised to resolve geographic disparity in liver transplantation and promote allocation based on medical urgency. At the time of writing, United Network for Organ Sharing is considering redistricting the organ procurement and transplantation network so that patient model for end-stage liver disease scores at transplant is more uniform across regions. We review the proposal with a systems-engineering focus and find that although the proposal is promising, it currently lacks evidence that it would perform effectively under realistic departures from its underlying data and assumptions. Moreover, we caution against prematurely focusing on redistricting as the only method to mitigate disparity. We describe system modeling principles which, if followed, will ensure that the redesigned allocation system is effective and efficient in achieving the intended goals. Abstract : Geographic disparities and liver allocation, simulation testing reality: This review describes the basic mathematics and computational hurdles in deriving a robust liver allocation system. Supplemental digital content is available in the text.